2014
DOI: 10.1089/vbz.2013.1564
|View full text |Cite
|
Sign up to set email alerts
|

Blood Meal Analysis and Virus Detection in Blood-Fed Mosquitoes Collected During the 2006–2007 Rift Valley Fever Outbreak in Kenya

Abstract: This study has demonstrated that RVFV and NDUV were concurrently circulating during the outbreak, and sheep and goats were the main amplifiers of these viruses respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 40 publications
2
59
0
1
Order By: Relevance
“…sudanensis, and Cx. rubinotus (Crabtree et al 2009, Ochieng et al 2013Lutomiah et al 2014. This means that the (potential) vectors of NDUV are more than is currently recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sudanensis, and Cx. rubinotus (Crabtree et al 2009, Ochieng et al 2013Lutomiah et al 2014. This means that the (potential) vectors of NDUV are more than is currently recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Masembe et al (2012) demonstrated the domestic pig (Sus scrofa) as a potential vertebrate host for NDUV while Lwande et al (2013) isolated NDUV from Rhipicephalus pulchellus collected from cattle (Bos taurus) and warthog (Phacochoerus africanus), although it is possible that this virus was in the blood meals from infected animals. It has also been suggested that goats are involved in the natural maintenance and ampliÞcation of NDUV (Lutomiah et al, 2014). This signiÞes the potential of NDUV maintenance by livestock as well as wild animals.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of mosquitoes have been identified as vectors [73,74]. Some Aedes species act as reservoirs for the virus during inter-epidemic periods, and increased rainfall in dry areas leads to an explosive hatching of mosquito eggs, many of which contain the virus.…”
Section: • Rift Valley Fevermentioning
confidence: 99%
“…The infected Aedes spp. feed preferentially on domestic ruminants which act as an amplifier of the virus [74]. Humans infect themselves through direct or indirect (aerosols) contact with blood, secretions or tissues of infected animals, which occurs in veterinary procedures (obstetrical manoeuvres, medical treatments), animal husbandry [75], slaughtering, consumption of raw milk and in food preparation.…”
Section: • Rift Valley Fevermentioning
confidence: 99%
“…Bloodmeal identification of field-collected vectors is pivotal to disentangling disease transmission dynamics, identifying ecological reservoirs during inter-epidemic periods, and developing appropriate disease control and response strategies [3]. However, most standard approaches to bloodmeal analysis rely on time consuming and expensive sequencing [4][5][6]. Peña et al (2012) developed an improved, cost-effective and rapid approach based on high resolution melting analysis (HRM) of cytochrome b (cyt b) Polymerase Chain Reaction (PCR) products to identify vertebrate bloodmeals of triatomine bugs (Rhodnius and Triatoma species) in the Caribbean region of Colombia [7].…”
Section: Introductionmentioning
confidence: 99%